2012
DOI: 10.1080/09291016.2011.599630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of television on sleep habits

Abstract: Television is the most widespread communication system of modern society, however, excessive television viewing have long-lasting adverse effects on health. The objective of this study was to investigate the impact of television on sleep behavior of human population of Chhattisgarh, India. The study have been conducted on 2105 individuals from remote (without electricity and television), rural, and urban areas. The rural population was further divided in two groups (i) people having electrical facility but no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The majority of studies ( n = 117) reported on one or more correlates of leisure SB (unpublished results: Araujo, Kastorini, Leite, Martinez‐Gomez, Reeves, Rosenkranz, Saidj and Silva). Table (summary) and Table S3 (individual leisure SBs) provides a summary of the evidence across all correlates and leisure SBs (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies ( n = 117) reported on one or more correlates of leisure SB (unpublished results: Araujo, Kastorini, Leite, Martinez‐Gomez, Reeves, Rosenkranz, Saidj and Silva). Table (summary) and Table S3 (individual leisure SBs) provides a summary of the evidence across all correlates and leisure SBs (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…However, increased artificial light exposure is known to have adverse effect on sleep health, reducing its quality and increasing the day time sleepiness. 6 , 7 Alteration in melatonin hormone, the chronobiotic conveying information about night/dark and therefore sleep timing to the brain, is known to be maximally affected by the latenight artificial light exposure. 8 Besides, higher screen time is also correlated to reduced physical activity level that interferes with the sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning chronotype, only the oldest group showed a significant difference compared to others, suggesting that the age-related changes are less pronounced compared to northern countries . Some studies reported that total sleep time decreases with age (Carrier et al ., 1997;Ohayon et al, 2004). Carrier et al (1997) finally concluded that both age and morningness contribute to habitual sleep patterns .…”
Section: Discussionmentioning
confidence: 99%
“…This study did not focus on chronotype though . Most of our knowledge about the sleep-wake cycle stems from countries of the northern hemisphere, especially the US, Europe, Japan and Taiwan or from Australasia (Carrier, Monk, Buysse, & Kupfer, 1997;Gradisar, Gardner, & Dohnt, 2011;Ishihara, Miyake, Myasita, & Miyata, 1988;Ohayon, Carskadon, Guilleminault, Vitiello, & others, 2004;Park, Matsumoto, Seo, Shinkoda, & Park, 1997;Taillard, Philip, Chastang, & Bioulac, 2004;Tonetti, Fabbri, & Natale, 2008;Vinha, Cavalcante, & Andrade, 2002) .…”
Section: Introductionmentioning
confidence: 99%